2005
DOI: 10.1089/acm.2005.11.813
|View full text |Cite
|
Sign up to set email alerts
|

Research on Homeopathy: State of the Art

Abstract: In this paper, we review research on homeopathy from four perspectives, focusing on reviews and some landmark studies. These perspectives are laboratory studies, clinical trials, observational studies, and theoretical work. In laboratory models, numerous effects and anomalies have been reported. However, no single model has been sufficiently widely replicated. Instead, researchers have focused on ever-new models and experiments, leaving the picture of scattered anomalies without coherence. Basic research, tryi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
72
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(76 citation statements)
references
References 149 publications
(117 reference statements)
0
72
0
4
Order By: Relevance
“…Starting from the algebraic formulation of physical quantum theory and discarding from its axioms elements appearing to be special to physics, a formalism was obtained which is applicable far beyond the realm of physics and still rich enough to attribute a well defined formal meaning to the notions of complementarity and entanglement beyond physics. Meanwhile, quite a few applications demonstrating a partial structural isomorphy to quantum physics in rather diverse situations have been worked out in more or less detail (see Atmanspacher et al 2002Atmanspacher et al , 2004Atmanspacher et al , 2006Atmanspacher et al , 2008aRömer 2004Römer , 2006Römer , 2007Römer , 2008Römer and Walach 2008;Walach and Römer 2009;von Lucadou et al 2007;von Lucadou and Römer 2010;Walach 2002Walach , 2005.…”
Section: Introductionmentioning
confidence: 99%
“…Starting from the algebraic formulation of physical quantum theory and discarding from its axioms elements appearing to be special to physics, a formalism was obtained which is applicable far beyond the realm of physics and still rich enough to attribute a well defined formal meaning to the notions of complementarity and entanglement beyond physics. Meanwhile, quite a few applications demonstrating a partial structural isomorphy to quantum physics in rather diverse situations have been worked out in more or less detail (see Atmanspacher et al 2002Atmanspacher et al , 2004Atmanspacher et al , 2006Atmanspacher et al , 2008aRömer 2004Römer , 2006Römer , 2007Römer , 2008Römer and Walach 2008;Walach and Römer 2009;von Lucadou et al 2007;von Lucadou and Römer 2010;Walach 2002Walach , 2005.…”
Section: Introductionmentioning
confidence: 99%
“…The observed variability of 30th potency effect is an example of the variable effects observed in homeopathic research and discussed by Walach et al [44]; however, the potency chord responses in the replications showed a consistent decrease in toxicity compared with placebo. This suggests that the fluctuation in potency effect is a property of potency itself and not the biosensor assay method.…”
Section: (19-21) Modulation Of Optical Isomer Toxicity Using Potentizmentioning
confidence: 68%
“…In other words, if replications of experiments, say, with Vibrio fischeri are performed using single potencies (also called simplexes), then as has been the case in previous research in homeopathy, we would expect to see evidence of the variability of outcome described by Walach et al [44] and also recently by Endler et al [51].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…However, RCTs of individualized homeopathic treatment have to be of a much better quality in order to withstand the critics who equate homeopathy at best with placebo effect [26][27][28]. Conclusion and interpretation vary depending often on what one is willing to accept as scientific information [29] and further, as a result of bias in the scientific community against homeopathy, it is often easier to publish negative results on homeopathy in the peer-reviewed literature than positive ones [30]. Lack of mechanistic insights has often plagued homeopathy studies, such as the unexplained findings that homeopathic dilutions of anti-IgE antibodies cause human basophil degranulation [31] and homeopathic dilutions of histamine inhibit basophil activation [32].…”
Section: Introductionmentioning
confidence: 99%